Effects of flavonoid glycosides obtained from a Ginkgo biloba extract fraction on the physical and oxidative stabilities of oil-in-water emulsions prepared from a stripped structured lipid with a low omega-6 to omega-3 ratio. (1st May 2015) - Yang, Dan; Wang, Xiang-Yu; Gan, Lu-Jing; Zhang, Hua; Shin, Jung-Ah; Lee, Ki-Teak; Hong, Soon-Taek
Highlights: Flavonoid glycosides fraction was fractionated on a column packed with HP-20 resin. The fraction showed higher antioxidant capacity than a biflavone fraction. The O/W emulsion containing structured lipid with the fraction showed good stability. The fraction was effective in retarding the oxidation of the O/W emulsions. Abstract: In this study, we have produced a structured lipid with a low ω6/ω3 ratio by lipase-catalysed interesterification with perilla and grape seed oils (1:3, wt/wt). A Ginkgo biloba leaf extract was fractionated in a column packed with HP-20 resin, producing a flavonoid glycoside fraction (FA) and a biflavone fraction (FB). FA exhibited higher antioxidant capacity than FB, showing 58.4 mmol gallic acid equivalent (GAE)/g-of-total-phenol-content, 58.8 mg quercetin equivalent (QUE)/g-of-total-flavonoid-content, 4.5 mmol trolox/g-of-trolox-equivalent antioxidant capacity, 0.14 mg extract/mL-of-free-radical-scavenging-activity (DPPH assay, IC50 ), and 2.3 mmol Fe2 SO4 ·7H2 O/g-of-ferric-reducing-antioxidant-power. The oil-in-water emulsion containing the stripped structured lipid as an oil phase with FA exhibited the highest stability and the lowest oil globule diameters ( d 43 and d 32 ), where the aggregation was unnoticeable by Turbiscan and particle size analyses during 30 days of storage. Furthermore, FA was effective in retarding the oxidation of the emulsions.